Polymorphisms in the xylosyltransferase genes cause higher serum XT-I activity in patients with pseudoxanthoma elasticum (PXE) and are involved in a severe disease course. Issue 9 (29th March 2006) - Schön, S; Schulz, V; Prante, C; Hendig, D; Szliska, C; Kuhn, J; Kleesiek, K; Götting, C
Abstract : Background: Pseudoxanthoma elasticum (PXE) is a heritable connective tissue disorder caused by mutations in the ABCC6 gene. Fragmentation of elastic fibres and deposition of proteoglycans result in a highly variable clinical picture. The altered proteoglycan metabolism suggests that enzymes from this pathway function as genetic co-factors in the severity of PXE. Therefore, we propose the XYLT genes encoding xylosyltransferase I (XT-I) as the chain-initiating enzyme in the biosynthesis of proteoglycans and the highly homologous XT-II as potential candidate genes. Methods: We screened all XYLT exons in 65 German PXE patients using denaturing high performance liquid chromatography and analysed the influence of the variations on clinical characteristics. Results: We identified 22 variations in the XYLT genes. The missense variation p.A115S (XT-I) is associated with higher serum XT activity (p = 0.005). The amino acid substitution p.T801R (XT-II; c.2402C>G) occurs with significantly higher frequency in patients under 30 years of age at diagnosis (43% v 26%; p = 0.04); all PXE patients with this variation suffer from skin lesions compared to only 75% of the wild type patients (p = 0.002). c.166G>A, c.1569C>T, and c.2402C>G in the XYLT-II gene were found to be more frequent in patients with higher organ involvement (p = 0.04, p = 0.01, and p = 0.02, respectively). Conclusions: Here we show for the first time that variations in the XYLT-II gene are genetic co-factors in the severity of PXE. Furthermore, the higher XT activity in patients with the exchange p.A115S (XT-I) indicates that this polymorphism is a potential marker for increased remodelling of the extracellular matrix.